Soil structure degradation in patches of alfalfa fields - Miretti, Maria Celeste (2010)
Alfalfa (Medicago sativa) is the basic forage resource for milk production in the flat Pampa of the Santa Fe Province of Argentina. However, the presence of microrelief with patches threatens the expansion of the area cultivated with alfalfa. The lower productivity in the patches is attributed to the inferior soil physical quality. The objectives of this study were to quantify indicators of soil physical quality and to establish the soil properties that would affect the alfalfa productivity in patches (PA) and normal areas (NA). Additionally, the macro and micro nutrient contents in both areas were determined. The experiment was carried out on an Aquic Argiudoll. Eighteen sampling sites, nine in NA and nine in PA were established. At each site, undisturbed soil samples (5 × 5 cm cores) were collected to measure soil bulk density (Bd), soil resistance to root penetration (PR), effective stress (σ), the water release curve and the least limiting water range (LLWR). Disturbed soil samples were also taken to determine macro and micronutrient contents, and particle size distribution. Non differences were detected for soil chemical properties between PA and NA. Aggregate size distribution indicated predominance of small aggregates in PA. Bd, PR and s were higher in PA than in NA, while the LLWR was narrower. Inadequate aeration under conditions of excessive soil moisture and inappropriate soil mechanical resistance when the soil is dry would affect alfalfa productivity. The overall results indicate that the soil physical quality in PA is lower than in NA.